The Relationship Between Leadership, Educational Level and Emotional Intelligence: A Case Study in Bahrain - AlHashmei, Suhaila E.; Hajee, Zahra R. (Prabandhan: Indian Journal of Management, 2013)
The concepts of Leadership and Emotional Intelligence (EI) are recognized to be important elements in organizations today. These concepts include vision creation, goal accomplishments, ambition, self-awareness, character and skills in tuning into others' emotions through the ability to establish relationships and bonds. Little material is available on EI and leadership in the Gulf area. This paper examines the relationship between these two concepts within the context of the national and organizational culture in Bahrain. The research examines the relationship between leadership styles and the components of emotional intelligence (Self-awareness, Self-management, Social awareness and Social skills)as identified by Goleman (2000), in five major organizations in Bahrain. The research adopted a deductive approach using mixed methods of questionnaires (Emotional Competency Inventory and Managerial Style Inventory) and interviewed 103 executives and managers. The research findings established that: a) There is a relationship between the six leadership styles and emotional intelligence; b) Six leadership styles are used and applied; and the executives showed moderate levels of emotional intelligence; c) National and corporate culture influenced the relationship between leadership styles and emotional intelligence; d) The standardized tests used should be adjusted to suit the culture of Bahrain.